Educadorartista: encontros da educação, artes visuais e intercultura - Diehl, Viviane (2015)
The present thesis for Doctorate in Education, following the research line of formation, knowledge and professional development, which conducts the subject of education and interculture within the Federal University of Santa Maria‟s Post-graduation Program in Education has as its goal to understand how the constitution of the artist-educator can interfere in the intercultural education in Arts for the high school system. In order to do that, we posed the questions of identifying how the artist-educator is formed, of recognizing how his artistic and pedagogical process is organized, as well as understanding in which way this position can interfere in the intercultural education in Arts for the high school system. We conducted this research at the Rio Grande do Sul‟s Institute of Education, Science and Technology (IFRS in portuguese). The autobiographical narratives of the educators, themselves visual artists, are used to elaborate the present study‟s methodology in order to produce the necessary information for the research in a relational research conception. The chosen subjects of interest allowed us to understand the gatherings, which aim at the sharing of life‟s experimentation, of Arts and of culture, concepts that pass through the constitution of the artist-educator and his action that always poses aesthetic and pedagogical questions in an in-between place of freedom and inventive creation as a form of knowledge, aiming at an intercultural education where the student can be an active participator.